1999
DOI: 10.1104/pp.121.3.775
|View full text |Cite
|
Sign up to set email alerts
|

The SLENDER Gene of Pea Encodes a Gibberellin 2-Oxidase

Abstract: The amount of active gibberellin (GA) in plant tissues is determined in part by its rate of catabolism through oxidation at C-2. In pea (Pisum sativum L.) seeds, GA 2-oxidation is controlled by the SLN (SLENDER) gene, a mutation of which produces seedlings characterized by a slender or hyper-elongated phenotype. We cloned a GA 2-oxidase cDNA from immature pea seeds by screening an expression library for enzyme activity. The clone contained a full-length open reading frame encoding a protein of 327 amino acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 17 publications
1
105
0
3
Order By: Relevance
“…4) and was observed in several other plant species (for review, see Hedden and Phillips, 2000;Fleet and Sun, 2005). A positive feed-forward regulation as reported for GA 2-oxidase transcript levels from some other plant species (Martin et al, 1999;Thomas et al, 1999;Elliott et al, 2001) was not observed for CmGA2ox1 gene expression, similar to observations obtained with rice GA 2-oxidase (Sakamoto et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…4) and was observed in several other plant species (for review, see Hedden and Phillips, 2000;Fleet and Sun, 2005). A positive feed-forward regulation as reported for GA 2-oxidase transcript levels from some other plant species (Martin et al, 1999;Thomas et al, 1999;Elliott et al, 2001) was not observed for CmGA2ox1 gene expression, similar to observations obtained with rice GA 2-oxidase (Sakamoto et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…There is growing evidence for the presence of rootbased GA biosynthesis from many plant species, including pumpkin (Yamaguchi et al, 1996;Smith et al, 1998), pea (Pisum sativum; Lester et al, 1999;Martin et al, 1999;Elliott et al, 2001;Davidson et al, 2003Davidson et al, , 2004, Arabidopsis (Chiang et al, 1995;Silverstone et al, 1997;Thomas et al, 1999), and rice (Oryza sativa; Sakamoto et al, 2001Sakamoto et al, , 2004Monna et al, 2002;Sasaki et al, 2002;Kaneko et al, 2003;Itoh et al, 2004). In this study, we present direct evidence for GA biosynthesis in root tips of young pumpkin seedlings.…”
Section: Discussionmentioning
confidence: 54%
“…The pea (Pisum sativum) slender mutant contains a loss-of-function allele of a GA2ox gene, GA2ox1, that is normally active in developing seeds: mature seeds of the mutant have increased levels of GA 20 , which, after germination, is activated by 3b-hydroxylation, resulting in increased elongation of the seedling (Reid et al, 1992;Ross et al, 1993Ross et al, , 1995Lester et al, 1999;Martin et al, 1999). Loss of function of the Arabidopsis GA2ox2 gene increases GA 4 levels in dark-imbibed seeds and thereby promotes germination in the mutant (Yamauchi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization of the enzymes responsible for 2b-hydroxylation showed that, like the GA 20-oxidases and GA 3-oxidases, they belong to the soluble 2-oxoglutarate-dependent dioxygenase class (Griggs et al, 1991). Genes encoding GA 2-oxidases were first identified by screening cDNA expression libraries for 2b-hydroxylase activity (Lester et al, 1999;Martin et al, 1999;Thomas et al, 1999). Five Arabidopsis GA 2-oxidase genes (GA2ox1, -2, -3, -4, and -6; GA2ox5, At3g17203, is a pseudogene) have since been identified based on sequence homology, and their encoded enzyme activities have been confirmed by heterologous expression in Escherichia coli (Thomas et al, 1999;Hedden and Phillips, 2000;Wang et al, 2004;Jasinski et al, 2005), demonstrating that they were active against C 19 -GAs, such as the bioactive GAs, GA 4 and GA 1 , and their immediate precursors.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a recently characterized class of GA-catabolizing enzymes, the GA 2-oxidases, are involved in the irreversible conversion of active GAs and their precursors to inactive forms and potentially can be used to reduce the endogenous levels of active GAs. cDNAs that encode 2-oxidases were isolated recently from runner bean, Arabidopsis, pea, and rice (MacMillan et al, 1997;Lester et al, 1999;Martin et al, 1999;Thomas et al, 1999;Sakamoto et al, 2001) and shown to perform oxidation reactions at carbon 2 of various biologically active and inactive GAs in vitro. In addition, several ESTs from lotus, Medicago , maize, soybean, and tomato, and sequences from the Arabidopsis and rice genome-sequencing projects, have been identified as putative GA 2-oxidases (Elliott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%